Flexibility in highway noise management - Paslawski, Jerzy (Transport, 2009)
The problem of noise management was taken as a key element of our life comfort. An adequate noise mitigation plan must be elaborated and implemented for a number of potential noise sources. The general idea of FLENO‐MA2 (FLExibility NOise MAnagement for A2 POZNAN BY‐PASS) advisory system was based on flexibility options situated on different management levels. In the recent years, two significant noise sources have been established in Poznan agglomeration: POZNAN BY‐PASS A2 as a part of A2 highway (BERLIN‐MOSCOW) and the NATO aircraft base in Krzesiny. Both are situated in the urban area of Poznan city. Special emphasis will be placed on flexibility noise mitigation options as an example of operational decision‐aid. However, finding a compromise solution based on diffused (using the Internet) information about the noise map (will be present in the near future) is the second goal of this system.First published online: 27 Oct 2010